Experimental and quantum chemical study оn the DNA/protein binding and the biological activity of a rhodium(iii) complex with 1,2,4-triazole as an inert ligand - Petrović, Angelina; Živanović, Marko; Puchta, Ralph; Ćoćić, Dušan; Scheurer, Andreas; Milivojevic, Nevena; Bogojeski, Jovana (Dalton Transactions, 2020)
The synthesis and structural characterization of a newly synthesized mononuclear rhodium(iii) complex, Rhtrz, with a ligand (2,2,6-bis((4S,7R)-7,8,8-trimethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)pyridine) and a ligand of 1,2,4-triazole, are presented in this paper. The kinetic interactions of the Rhtrz complex with essential biomolecules such as 5-GMP, L-Met, and GSH were examined. The study of the biological interactions was focused on the binding properties of the Rhtrz complex with CT-DNA and serum albumin. These interactions were investigated using UV-vis spectrophotometry, fluorescence spectroscopy, viscosity measurements, thermal denaturation studies, and electrophoresis. Fluorescence competition experiments with site-markers for BSA were used to locate the binding site of the Rhtrz-complex to the BSA. Molecular docking studies were carried out to obtain detailed binding information of the complex with CT-DNA, BSA, and HSA. Furthermore, the apparent distance between the donor (HSA) and acceptor (Rhtrz) was determined using fluorescence resonance energy transfer (FRET). The thermodynamic properties and relative stabilities of the Rhtrz complex were examined, constructing the two model equation by DFT calculations (B3LYP(CPCM)/LANL2DZp). In vitro cytotoxicity and redox status on the human epithelial colorectal cancer cell line (HCT-116) and healthy human fibroblast cell line (MRC-5) were also investigated.
CRIS-Team Scopus Importer:2020-07-03